Authorial Stance in Black and Blue Novel by Anna Quindlin - Fadhil, Dhafar Jamal; Rezq-Allah, May Stephan (Al-Adab Journal, 2022)
The present study is concerned with the writer’s ideologies towards violence against women. The study will focus on analyzing an English novel about violence against women so as to see to what extent writers are being affected and influenced by their genders. It also focuses on showing to what extent writer’s ideologies are reflected in their works. Gender influence social groups ideologies; therefore, when a writer discusses an issue that concerns the other gender, they will be either subjective or objective depending on the degree of influence, i.e., gender has influenced their thoughts as well as behaviours. A single fact may be presented differently by different writers depending on the range of affectedness by ideologies. The study aims to uncover and reveal the hidden gender-based ideologies, by analyzing the discursive structure of a novel based on Van Dijk’s model (2000) of ideology and racism. The selected novel is based on discussing violence against women. The study will later on reveal what the real writer’s gender-based ideologies is. Is the writer feminist or anti-feminist? Is he prejudiced? Is he biased?.